Gender Representation in Indonesian EFL Coursebook for 12th Grade - Noviyanti, Sari Dewi (ELITE JOURNAL, 2024)
Gender representation in educational materials is a crucial aspect of fostering inclusivity and promoting social equity in the classroom. Ensuring accurate and equitable gender representation is needed to foster inclusive learning environments. This article presents the findings of a study which analyzed the gender representation within the latest English coursebook for senior high school students which adapt Kurikulum Merdeka and published by Indonesian Ministry of Education, Culture, Research and Technology. The data for this research extracted from reading passages and images in the English coursebook titled "Train of Thought”. To uncover disparities in power dynamics between genders, elements such as visual depictions, character representations, social roles, domestic duties, and semantic roles were analyzed. The investigation revealed a bias favoring men in certain roles and activities, such as athleticism, social engagement, and sports participation. Despite this, some equality was found in pictorial representation, activities, and roles. These findings underscore the importance of critically examining educational materials for gender biases and stereotypes, informing curriculum development and coursebook selection processes to promote gender equity and inclusivity in education